A kind of anti-aging PC / PP alloy and preparation method thereof

By adding compatibility agents and anti-aging fillers to the preparation of PC/PP alloy, the problems of poor compatibility and poor anti-aging performance of PC/PP alloy are solved, and the good anti-aging performance of the alloy is achieved.

CN118667319BActive Publication Date: 2025-03-18GUANGDONG SEONLON NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410762157.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-03-18
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

PC/PP alloys have poor compatibility, and are prone to form unstable morphological structures during blending, and have poor anti-aging performance.

Method used

In the preparation process of PC/PP alloy, the interfacial tension between PP and PC is improved and the anti-aging filler is evenly dispersed by high-speed mixing and screw extrusion granulation process.

Benefits of technology

The anti-aging performance of PC/PP alloy is significantly improved, so that its elongation rate of break and retention of notch impact strength in artificial accelerated aging test are significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an anti-aging PC / PP alloy and a preparation method thereof, and belongs to the technical field of polymer materials. The method comprises the following steps: mixing polycarbonate, polypropylene, a compatibilizer, stearic acid and an anti-aging filler in a high-speed mixer, extruding and granulating in a screw extruder to obtain the anti-aging PC / PP alloy; by adding the compatibilizer and the anti-aging filler, the compatibilizer greatly improves the interfacial tension between PP and PC during the blending process, and also makes the anti-aging filler uniformly dispersed in the blending system, so that the prepared PC / PP alloy has good anti-aging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an anti-aging PC / PP alloy and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is an important engineering plastic, which is widely used in many fields for its excellent physical properties and chemical stability. The molecular chain of PC contains -OR-CO-O-links, which give it good heat resistance, transparency and mechanical strength. According to the different types of R groups, PC can be divided into several categories such as aliphatic and aromatic. Among them, bisphenol A aromatic polycarbonate is the most well-known for its excellent comprehensive performance. However, despite the many advantages of PC, its disadvantages such as high melt viscosity and poor processability also restrict its application in some fields. Especially in the manufacturing process, PC products are more sensitive to notches, have poor resistance to environmental stress cracking, and poor solvent resistance. These problems make PC difficult to be competent in some occasions that require high processability and good environmental adaptability.

[0003] In order to improve the comprehensive performance of PC, researchers have tried to blend PC with other polymers to obtain blend materials with complementary properties. Among them, polypropylene (PP), as a widely used general-purpose thermoplastic, has become an ideal choice for blending with PC due to its low relative density, superior comprehensive performance, good corrosion resistance and processing performance, and low price. By blending PC and PP, researchers hope to reduce the melt viscosity of PC, improve its processing performance, and increase the notched impact strength of the product. At the same time, the raw material cost of this blend is relatively low, which helps to reduce production costs. However, the solubility parameters of PC and PP are very different, and the polarity difference is obvious, which makes the two thermodynamically incompatible. In terms of process, PC and PP are prone to form unstable morphological structures when simply blended, and the interfacial tension is large, resulting in poor mechanical properties. In addition, due to the poor compatibility of PC and PP, the anti-aging properties of the prepared PC / PP alloy are often unsatisfactory. These problems have become key factors limiting the application of PC / PP blends in a wider range of fields. Summary of the invention

[0004] The object of the present invention is to provide an anti-aging PC / PP alloy and a preparation method thereof, so as to solve the problems that the PC / PP alloy has poor compatibility, is prone to form an unstable morphological structure during blending, and has poor anti-aging performance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing an anti-aging PC / PP alloy comprises the following steps:

[0007] Polycarbonate, polypropylene, compatibilizer, stearic acid and anti-aging filler are mixed in a high-speed mixer at 350-450 r / min for 5-10 min, and extruded and granulated in a screw extruder at 200-240° C. to obtain the anti-aging PC / PP alloy.

[0008] As a preferred technical solution of the present invention, the mass ratio of the polycarbonate, polypropylene, compatibilizer, stearic acid and anti-aging filler is 40-55:35-45:4-10:1-2:0.8-1.2.

[0009] As a preferred technical solution of the present invention, the preparation of the anti-aging filler comprises the following steps:

[0010] S11, mix nano titanium dioxide and sodium hydroxide solution, ultrasonically disperse for 30-40 minutes, stir in dark for 8-10 hours, transfer to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, seal and place in a forced air drying oven at 145°C for 30-40 hours, cool to room temperature, centrifuge, wash the solid phase, dry, and calcine at 450°C for 2-3 hours to obtain material A;

[0011] S12, taking the material A and the silver nitrate solution, mixing, ultrasonically dispersing for 10-20 minutes, stirring for 8-10 hours, centrifuging, washing the solid phase, drying, and calcining at 450° C. for 1-2 hours to obtain material B;

[0012] S13, mixing graphene oxide powder, material B and deionized water, ultrasonically dispersing for 1-2 hours, transferring to a hydrothermal reactor and reacting at 110° C. for 2-3 hours, cooling, centrifuging, washing and drying the solid phase to obtain material C;

[0013] S14, taking the material C and deionized water, mixing, ultrasonically dispersing for 30-40 minutes, to obtain material D; taking polyglutamic acid and sodium hydroxide solution, mixing, stirring for 20-30 minutes, to obtain material E; adding the material E to the material D while stirring, and then ultrasonically dispersing for 15-25 minutes, stirring at room temperature in a nitrogen atmosphere for 18-24 hours, drying, and grinding to obtain modified graphene oxide;

[0014] S15, zinc oxide nanorods, sodium polyacrylate and deionized water are mixed, ultrasonically dispersed for 35-45 minutes to obtain material F, and the material F is set aside; the modified graphene oxide is placed in the material F, sodium dodecyl sulfate is added, stirred in a water bath at 45° C. for 3-4 hours, filtered, and the precipitate is dried to obtain the anti-aging filler.

[0015] As a preferred technical solution of the present invention, in step S11, the dosage ratio of the nano-titanium dioxide and the sodium hydroxide solution is 0.6-0.8 g: 60-80 mL; and the concentration of the sodium hydroxide solution is 10 mol / L.

[0016] As a preferred technical solution of the present invention, in step S12, the dosage ratio of the material A and the silver nitrate solution is 0.8-1.2 g: 100-120 mL; and the concentration of the silver nitrate solution is 0.1 mol / L.

[0017] As a preferred technical solution of the present invention, in step S13, the mass ratio of the graphene oxide powder, material B, and deionized water is 0.15-0.25:0.8-1.2:200.

[0018] As a preferred technical solution of the present invention, in step S14, the dosage ratio of the material C, deionized water, polyglutamic acid, and sodium hydroxide solution is 0.8-1.2 g: 150-200 mL: 2-3 g: 50-80 mL; the concentration of the sodium hydroxide solution is 4 mg / mL.

[0019] As a preferred technical solution of the present invention, in step S15, the mass ratio of the zinc oxide nanorods, sodium polyacrylate, deionized water, modified graphene oxide, and sodium dodecyl sulfate is 0.5-0.6: 0.005-0.006: 50: 0.83-1.25: 0.004-0.006.

[0020] As a preferred technical solution of the present invention, the preparation of the compatibilizer comprises the following steps:

[0021] S21, take solid hydrochloric acid and acetone, mix them, add epoxidized soybean oil, stir at 45 ° C for 15-20 minutes, then cool to 40 ° C and continue stirring for 2-3 hours, add ethyl acetate and deionized water, take the organic phase after layering, wash, dry, filter, and remove acetone by vacuum distillation to obtain material G; the dosage ratio of solid hydrochloric acid, acetone, epoxidized soybean oil, ethyl acetate, and deionized water is 50-52g: 200mL: 74-76g: 200mL: 120-130mL;

[0022] S22, take polystyrene-block-methyl methacrylate (purchased from Hangzhou Yuhao Chemical Technology Co., Ltd.), inhibitor 701 (purchased from Nanjing Huikang Biotechnology Co., Ltd.), epoxy soybean oil, mix, stir for 15-20min, heat to 85-95°C, add acrylic acid and triphenylphosphine, stir for 2-3h, heat to 110-120°C for reaction for 5-6h, cool, then introduce into butanone, filter, take the liquid phase and introduce into petroleum ether for standing for 6-8h, filter, take the solid phase and dry to obtain material H; the dosage ratio of polystyrene-block-methyl methacrylate, inhibitor 701, epoxy soybean oil, acrylic acid, triphenylphosphine, butanone and petroleum ether is 30-40g: 0.04-0.06g: 80-100g: 25-30g: 2.2-2.3g: 200mL: 200mL;

[0023] S23, in a nitrogen atmosphere, take the material G, material H, isophorone diisocyanate, 2,2-dimethylol propionic acid, mix, and stir at 75-85 ° C for 2-3 hours, cool to room temperature, add sodium dodecyl sulfate-potassium persulfate-deionized water mixture, stir for 15-20 minutes, add methyl methacrylate and butyl acrylate, stir for 20-30 minutes, heat to 75-85 ° C and stir for 4-6 hours, filter, and take the liquid phase to obtain the compatibilizer; the material G, material H The mass ratio of isophorone diisocyanate, 2,2-dihydroxymethylpropionic acid, sodium dodecyl sulfate-potassium persulfate-deionized water mixture, methyl methacrylate, and butyl acrylate is 9-15:12-20:14-18:4-6:80-82:10-12:7-9; the mass ratio of sodium dodecyl sulfate, potassium persulfate, and deionized water in the sodium dodecyl sulfate-potassium persulfate-deionized water mixture is 0.5-0.7:0.15-0.25:79-80.

[0024] The anti-aging PC / PP alloy is prepared by the above preparation method.

[0025] Beneficial effects of the present invention:

[0026] The present invention discloses an anti-aging PC / PP alloy and a preparation method thereof. By adding a compatibilizer and an anti-aging filler, the compatibilizer greatly improves the interfacial tension between PP and PC during the blending process, and also makes the anti-aging filler uniformly dispersed in the blending system, so that the prepared PC / PP alloy has good anti-aging performance. DETAILED DESCRIPTION

[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0028] Example 1

[0029] A method for preparing an anti-aging PC / PP alloy comprises the following steps:

[0030] Polycarbonate, polypropylene, compatibilizer, stearic acid and anti-aging filler are mixed in a high-speed mixer at 350 r / min for 10 min, and extruded and granulated in a screw extruder at 200° C. to obtain the anti-aging PC / PP alloy; the mass ratio of the polycarbonate, polypropylene, compatibilizer, stearic acid and anti-aging filler is 40:35:4:1:0.8;

[0031] The preparation of the anti-aging filler comprises the following steps:

[0032] S11, mix nano titanium dioxide and sodium hydroxide solution, ultrasonically disperse for 30 minutes, stir in dark place for 8 hours, transfer to a stainless steel hydrothermal reactor with polytetrafluoroethylene lining, seal and place in a blast drying oven, keep constant temperature at 145°C for 30 hours, cool to room temperature, centrifuge, wash the solid phase, dry, and calcine at 450°C for 2 hours to obtain material A; the dosage ratio of the nano titanium dioxide and sodium hydroxide solution is 0.6g:60mL; the concentration of the sodium hydroxide solution is 10mol / L;

[0033] S12, taking the material A and the silver nitrate solution, mixing, ultrasonically dispersing for 10 minutes, stirring for 8 hours, centrifuging, washing the solid phase, drying, and calcining at 450° C. for 1 hour to obtain material B; the dosage ratio of the material A to the silver nitrate solution is 0.8 g:100 mL; the concentration of the silver nitrate solution is 0.1 mol / L;

[0034] S13, mixing graphene oxide powder, material B and deionized water, ultrasonically dispersing for 1 hour, transferring to a hydrothermal reactor and reacting at 110° C. for 2 hours, cooling, centrifuging, washing and drying the solid phase to obtain material C; the mass ratio of the graphene oxide powder, material B and deionized water is 0.15:0.8:200;

[0035] S14, take the material C and deionized water, mix them, and ultrasonically disperse them for 30 minutes to obtain material D; take polyglutamic acid and sodium hydroxide solution, mix them, and stir them for 20 minutes to obtain material E; add the material E to the material D while stirring, and then ultrasonically disperse it for 15 minutes, stir it at room temperature in a nitrogen atmosphere for 18 hours, dry it, and grind it to obtain modified graphene oxide; the dosage ratio of the material C, deionized water, polyglutamic acid, and sodium hydroxide solution is 0.8g:150mL:2g:50mL; the concentration of the sodium hydroxide solution is 4mg / mL;

[0036] S15, zinc oxide nanorods, sodium polyacrylate, and deionized water are mixed, and ultrasonic dispersion is performed for 35 minutes to obtain material F for standby use; the modified graphene oxide is placed in the material F, sodium dodecyl sulfate is added, and the mixture is stirred in a water bath at 45° C. for 3 hours, filtered, and the precipitate is dried to obtain the anti-aging filler; the mass ratio of the zinc oxide nanorods, sodium polyacrylate, deionized water, modified graphene oxide, and sodium dodecyl sulfate is 0.5:0.005:50:0.83:0.004;

[0037] The preparation of the compatibilizer comprises the following steps:

[0038] S21, take solid hydrochloric acid and acetone, mix them, add epoxidized soybean oil, stir at 45°C for 15min, then cool to 40°C and continue stirring for 2h, add ethyl acetate and deionized water, wash the organic phase after stratification, dry, filter, and remove acetone by vacuum distillation to obtain material G; the dosage ratio of solid hydrochloric acid, acetone, epoxidized soybean oil, ethyl acetate, and deionized water is 50g:200mL:74g:200mL:120mL;

[0039] S22, take polystyrene-block-methyl methacrylate, inhibitor 701, and epoxy soybean oil, mix, stir for 15 minutes, heat to 85°C, add acrylic acid and triphenylphosphine, stir for 2 hours, heat to 110°C for reaction for 5 hours, cool, then introduce into butanone, filter, take the liquid phase and introduce into petroleum ether and let stand for 6 hours, filter, take the solid phase and dry to obtain material H; the dosage ratio of polystyrene-block-methyl methacrylate, inhibitor 701, epoxy soybean oil, acrylic acid, triphenylphosphine, butanone, and petroleum ether is 30g:0.04g:80g:25g:2.2g:200mL:200mL;

[0040] S23. In a nitrogen atmosphere, mix the material G, material H, isophorone diisocyanate and 2,2-dimethylolpropionic acid, stir at 75°C for 2h, cool to room temperature, add a mixture of sodium dodecyl sulfate-potassium persulfate-deionized water, stir for 15min, add methyl methacrylate and butyl acrylate, stir for 20min, heat to 75°C and stir for 4h, filter, and take the liquid phase to obtain the compatibilizer; the mass ratio of the material G, material H, isophorone diisocyanate, 2,2-dimethylolpropionic acid, a mixture of sodium dodecyl sulfate-potassium persulfate-deionized water, methyl methacrylate and butyl acrylate is 9:12:14:4:80:10:7; the mass ratio of sodium dodecyl sulfate, potassium persulfate and deionized water in the sodium dodecyl sulfate-potassium persulfate-deionized water mixture is 0.5:0.15:79.

[0041] Example 2

[0042] A method for preparing an anti-aging PC / PP alloy comprises the following steps:

[0043] Polycarbonate, polypropylene, compatibilizer, stearic acid and anti-aging filler are mixed in a high-speed mixer at 400 r / min for 8 minutes, and extruded and granulated in a screw extruder at 220° C. to obtain the anti-aging PC / PP alloy; the mass ratio of the polycarbonate, polypropylene, compatibilizer, stearic acid and anti-aging filler is 48:40:7:1.5:1;

[0044] The preparation of the anti-aging filler comprises the following steps:

[0045] S11, mix nano titanium dioxide and sodium hydroxide solution, ultrasonically disperse for 35 minutes, stir in dark for 9 hours, transfer to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, seal and place in a blast drying oven, keep a constant temperature of 145°C for 35 hours, cool to room temperature, centrifuge, wash the solid phase, dry, and calcine at 450°C for 2.5 hours to obtain material A; the dosage ratio of the nano titanium dioxide and sodium hydroxide solution is 0.8g:70mL; the concentration of the sodium hydroxide solution is 10mol / L;

[0046] S12, taking the material A and the silver nitrate solution, mixing, ultrasonically dispersing for 15 minutes, stirring for 9 hours, centrifuging, washing the solid phase, drying, and calcining at 450° C. for 1.5 hours to obtain material B; the amount ratio of the material A and the silver nitrate solution is 1g:110mL; the concentration of the silver nitrate solution is 0.1mol / L;

[0047] S13, mixing graphene oxide powder, material B and deionized water, ultrasonically dispersing for 1.5 hours, transferring to a hydrothermal reactor and reacting at 110° C. for 2.5 hours, cooling, centrifuging, washing and drying the solid phase to obtain material C; the mass ratio of the graphene oxide powder, material B and deionized water is 0.2:1:200;

[0048] S14, take the material C and deionized water, mix them, and ultrasonically disperse them for 35 minutes to obtain material D; take polyglutamic acid and sodium hydroxide solution, mix them, and stir them for 25 minutes to obtain material E; add the material E to the material D while stirring, then ultrasonically disperse it for 20 minutes, stir it at room temperature and in a nitrogen atmosphere for 20 hours, dry it, and grind it to obtain modified graphene oxide; the dosage ratio of the material C, deionized water, polyglutamic acid, and sodium hydroxide solution is 1g:180mL:2.5g:65mL; ​​the concentration of the sodium hydroxide solution is 4mg / mL;

[0049] S15, zinc oxide nanorods, sodium polyacrylate, and deionized water are mixed, and ultrasonic dispersion is performed for 40 minutes to obtain material F for standby use; the modified graphene oxide is placed in the material F, sodium dodecyl sulfate is added, and the mixture is stirred in a water bath at 45° C. for 3.5 hours, filtered, and the precipitate is dried to obtain the anti-aging filler; the mass ratio of the zinc oxide nanorods, sodium polyacrylate, deionized water, modified graphene oxide, and sodium dodecyl sulfate is 0.55:0.0055:50:1.05:0.005;

[0050] The preparation of the compatibilizer comprises the following steps:

[0051] S21, take solid hydrochloric acid and acetone, mix them, add epoxidized soybean oil, stir at 45°C for 18min, then cool to 40°C and continue stirring for 2.5h, add ethyl acetate and deionized water, wash the organic phase after stratification, dry, filter, and remove acetone by vacuum distillation to obtain material G; the dosage ratio of solid hydrochloric acid, acetone, epoxidized soybean oil, ethyl acetate, and deionized water is 51g:200mL:75g:200mL:125mL;

[0052] S22, take polystyrene-block-methyl methacrylate, inhibitor 701, and epoxy soybean oil, mix, stir for 18 minutes, heat to 90°C, add acrylic acid and triphenylphosphine, stir for 2.5 hours, heat to 115°C, react for 5.5 hours, cool, then introduce into butanone, filter, take the liquid phase and introduce into petroleum ether and let stand for 7 hours, filter, take the solid phase and dry to obtain material H; the dosage ratio of polystyrene-block-methyl methacrylate, inhibitor 701, epoxy soybean oil, acrylic acid, triphenylphosphine, butanone, and petroleum ether is 35g:0.05g:90g:28g:2.25g:200mL:200mL;

[0053] S23. In a nitrogen atmosphere, mix the material G, material H, isophorone diisocyanate and 2,2-dimethylolpropionic acid, stir at 80°C for 2.5h, cool to room temperature, add a mixture of sodium dodecyl sulfate-potassium persulfate-deionized water, stir for 18min, add methyl methacrylate and butyl acrylate, stir for 25min, heat to 80°C and stir for 5h, filter, and take the liquid phase to obtain the compatibilizer; the mass ratio of the material G, material H, isophorone diisocyanate, 2,2-dimethylolpropionic acid, a mixture of sodium dodecyl sulfate-potassium persulfate-deionized water, methyl methacrylate and butyl acrylate is 12:16:16:5:81:11:8; the mass ratio of sodium dodecyl sulfate, potassium persulfate and deionized water in the sodium dodecyl sulfate-potassium persulfate-deionized water mixture is 0.6:0.2:79.5.

[0054] Example 3

[0055] A method for preparing an anti-aging PC / PP alloy comprises the following steps:

[0056] Polycarbonate, polypropylene, compatibilizer, stearic acid and anti-aging filler are mixed in a high-speed mixer at 450 r / min for 5 minutes, and extruded and granulated in a screw extruder at 240° C. to obtain the anti-aging PC / PP alloy; the mass ratio of polycarbonate, polypropylene, compatibilizer, stearic acid and anti-aging filler is 55:45:10:2:1.2;

[0057] The preparation of the anti-aging filler comprises the following steps:

[0058] S11, mix nano titanium dioxide and sodium hydroxide solution, ultrasonically disperse for 40 minutes, stir in dark for 10 hours, transfer to a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, seal and place in a blast drying oven, keep a constant temperature of 145°C for 40 hours, cool to room temperature, centrifuge, wash the solid phase, dry, and calcine at 450°C for 3 hours to obtain material A; the dosage ratio of the nano titanium dioxide and sodium hydroxide solution is 0.8g:80mL; the concentration of the sodium hydroxide solution is 10mol / L;

[0059] S12, taking the material A and the silver nitrate solution, mixing, ultrasonically dispersing for 20 minutes, stirring for 10 hours, centrifuging, washing the solid phase, drying, and calcining at 450° C. for 2 hours to obtain material B; the dosage ratio of the material A to the silver nitrate solution is 1.2 g: 120 mL; the concentration of the silver nitrate solution is 0.1 mol / L;

[0060] S13, mixing graphene oxide powder, material B and deionized water, ultrasonically dispersing for 2 hours, transferring to a hydrothermal reactor and reacting at 110° C. for 3 hours, cooling, centrifuging, washing and drying the solid phase to obtain material C; the mass ratio of the graphene oxide powder, material B and deionized water is 0.25:1.2:200;

[0061] S14, taking the material C and deionized water, mixing, ultrasonically dispersing for 40 minutes, to obtain material D; taking polyglutamic acid and sodium hydroxide solution, mixing, stirring for 30 minutes, to obtain material E; adding the material E to the material D while stirring, and then ultrasonically dispersing for 25 minutes, stirring for 24 hours at room temperature in a nitrogen atmosphere, drying, grinding, and obtaining modified graphene oxide; the amount ratio of the material C, deionized water, polyglutamic acid, and sodium hydroxide solution is 1.2g:200mL:3g:80mL; the concentration of the sodium hydroxide solution is 4mg / mL;

[0062] S15, zinc oxide nanorods, sodium polyacrylate, and deionized water are mixed, and ultrasonic dispersion is performed for 45 minutes to obtain material F for standby use; the modified graphene oxide is placed in the material F, sodium dodecyl sulfate is added, and the mixture is stirred in a water bath at 45° C. for 4 hours, filtered, and the precipitate is dried to obtain the anti-aging filler; the mass ratio of the zinc oxide nanorods, sodium polyacrylate, deionized water, modified graphene oxide, and sodium dodecyl sulfate is 0.6:0.006:50:1.25:0.006;

[0063] The preparation of the compatibilizer comprises the following steps:

[0064] S21, take solid hydrochloric acid and acetone, mix them, add epoxidized soybean oil, stir at 45°C for 20min, then cool to 40°C and continue stirring for 3h, add ethyl acetate and deionized water, wash the organic phase after stratification, dry, filter, and remove acetone by vacuum distillation to obtain material G; the dosage ratio of solid hydrochloric acid, acetone, epoxidized soybean oil, ethyl acetate, and deionized water is 52g:200mL:76g:200mL:130mL;

[0065] S22, take polystyrene-block-methyl methacrylate, inhibitor 701, and epoxy soybean oil, mix, stir for 20 minutes, heat to 95°C, add acrylic acid and triphenylphosphine, stir for 3 hours, heat to 120°C for reaction for 6 hours, cool, then introduce into butanone, filter, take the liquid phase and introduce into petroleum ether and let stand for 8 hours, filter, take the solid phase and dry to obtain material H; the dosage ratio of polystyrene-block-methyl methacrylate, inhibitor 701, epoxy soybean oil, acrylic acid, triphenylphosphine, butanone, and petroleum ether is 40g:0.06g:100g:30g:2.3g:200mL:200mL;

[0066] S23. In a nitrogen atmosphere, mix the material G, material H, isophorone diisocyanate and 2,2-dimethylolpropionic acid, stir at 85°C for 3h, cool to room temperature, add a mixture of sodium dodecyl sulfate-potassium persulfate-deionized water, stir for 20min, add methyl methacrylate and butyl acrylate, stir for 30min, heat to 85°C and stir for 6h, filter, and take the liquid phase to obtain the compatibilizer; the mass ratio of the material G, material H, isophorone diisocyanate, 2,2-dimethylolpropionic acid, a mixture of sodium dodecyl sulfate-potassium persulfate-deionized water, methyl methacrylate and butyl acrylate is 15:20:18:6:82:12:9; the mass ratio of sodium dodecyl sulfate, potassium persulfate and deionized water in the sodium dodecyl sulfate-potassium persulfate-deionized water mixture is 0.7:0.25:80.

[0067] Comparative Example 1

[0068] The difference from Example 1 is that the preparation of the anti-aging filler comprises the following steps:

[0069] S11, mixing graphene oxide powder, silver nitrate solution and deionized water, ultrasonically dispersing for 1 hour, transferring to a hydrothermal reactor and reacting at 110° C. for 2 hours, cooling, centrifuging, washing and drying the solid phase to obtain material C; the mass ratio of the graphene oxide powder, silver nitrate solution and deionized water is 0.15:0.8:200;

[0070] S12, take the material C and deionized water, mix them, and ultrasonically disperse them for 30 minutes to obtain material D; take polyglutamic acid and sodium hydroxide solution, mix them, and stir them for 20 minutes to obtain material E; add the material E to the material D while stirring, and then ultrasonically disperse it for 15 minutes, stir it at room temperature and in a nitrogen atmosphere for 18 hours, dry it, and grind it to obtain modified graphene oxide; the dosage ratio of the material C, deionized water, polyglutamic acid, and sodium hydroxide solution is 0.8g:150mL:2g:50mL; the concentration of the sodium hydroxide solution is 4mg / mL;

[0071] S13, zinc oxide nanorods, sodium polyacrylate, and deionized water are mixed, ultrasonically dispersed for 35 minutes, and material F is obtained for standby use; the modified graphene oxide is placed in the material F, sodium dodecyl sulfate is added, and the mixture is stirred in a water bath at 45°C for 3 hours, filtered, and the precipitate is dried to obtain the anti-aging filler; the mass ratio of the zinc oxide nanorods, sodium polyacrylate, deionized water, modified graphene oxide, and sodium dodecyl sulfate is 0.5:0.005:50:0.83:0.004.

[0072] Comparative Example 2

[0073] The difference from Example 1 is that the preparation of the anti-aging filler comprises the following steps:

[0074] S11, mix nano titanium dioxide and sodium hydroxide solution, ultrasonically disperse for 30 minutes, stir in dark place for 8 hours, transfer to a stainless steel hydrothermal reactor with polytetrafluoroethylene lining, seal and place in a blast drying oven, keep constant temperature at 145°C for 30 hours, cool to room temperature, centrifuge, wash the solid phase, dry, and calcine at 450°C for 2 hours to obtain material A; the dosage ratio of the nano titanium dioxide and sodium hydroxide solution is 0.6g:60mL; the concentration of the sodium hydroxide solution is 10mol / L;

[0075] S12, mixing graphene oxide powder, material A and deionized water, ultrasonically dispersing for 1 hour, transferring to a hydrothermal reactor and reacting at 110° C. for 2 hours, cooling, centrifuging, washing and drying the solid phase to obtain material C; the mass ratio of the graphene oxide powder, material A and deionized water is 0.15:0.8:200;

[0076] S13, take the material C and deionized water, mix them, and ultrasonically disperse them for 30 minutes to obtain material D; take polyglutamic acid and sodium hydroxide solution, mix them, and stir them for 20 minutes to obtain material E; add the material E to the material D while stirring, and then ultrasonically disperse it for 15 minutes, stir it at room temperature and in a nitrogen atmosphere for 18 hours, dry it, and grind it to obtain modified graphene oxide; the dosage ratio of the material C, deionized water, polyglutamic acid, and sodium hydroxide solution is 0.8g:150mL:2g:50mL; the concentration of the sodium hydroxide solution is 4mg / mL;

[0077] S14, zinc oxide nanorods, sodium polyacrylate, and deionized water are mixed, and ultrasonically dispersed for 35 minutes to obtain material F for standby use; the modified graphene oxide is placed in the material F, sodium dodecyl sulfate is added, and the mixture is stirred in a water bath at 45°C for 3 hours, filtered, and the precipitate is dried to obtain the anti-aging filler; the mass ratio of the zinc oxide nanorods, sodium polyacrylate, deionized water, modified graphene oxide, and sodium dodecyl sulfate is 0.5:0.005:50:0.83:0.004.

[0078] Comparative Example 3

[0079] The difference from Example 1 is that the preparation of the anti-aging filler comprises the following steps:

[0080] S11, mix nano titanium dioxide and sodium hydroxide solution, ultrasonically disperse for 30 minutes, stir in dark place for 8 hours, transfer to a stainless steel hydrothermal reactor with polytetrafluoroethylene lining, seal and place in a blast drying oven, keep constant temperature at 145°C for 30 hours, cool to room temperature, centrifuge, wash the solid phase, dry, and calcine at 450°C for 2 hours to obtain material A; the dosage ratio of the nano titanium dioxide and sodium hydroxide solution is 0.6g:60mL; the concentration of the sodium hydroxide solution is 10mol / L;

[0081] S12, taking the material A and the silver nitrate solution, mixing, ultrasonically dispersing for 10 minutes, stirring for 8 hours, centrifuging, washing the solid phase, drying, and calcining at 450° C. for 1 hour to obtain material B; the dosage ratio of the material A to the silver nitrate solution is 0.8 g:100 mL; the concentration of the silver nitrate solution is 0.1 mol / L;

[0082] S13, mixing graphene oxide powder, material B and deionized water, ultrasonically dispersing for 1 hour, transferring to a hydrothermal reactor and reacting at 110° C. for 2 hours, cooling, centrifuging, washing and drying the solid phase to obtain material C; the mass ratio of the graphene oxide powder, material B and deionized water is 0.15:0.8:200;

[0083] S14, taking the material C and deionized water, mixing, ultrasonically dispersing for 30 minutes, obtaining material D, stirring for 18 hours at room temperature in a nitrogen atmosphere, drying, grinding, and obtaining modified graphene oxide; the amount ratio of the material C and deionized water is 0.8g:150mL;

[0084] S15. Mix zinc oxide nanorods, sodium polyacrylate and deionized water, and ultrasonically disperse them for 35 minutes to obtain material F for standby use; take the modified graphene oxide and place it in the material F, add sodium dodecyl sulfate, stir in a water bath at 45°C for 3 hours, filter, take the precipitate and dry it to obtain the anti-aging filler; the mass ratio of the zinc oxide nanorods, sodium polyacrylate, deionized water, modified graphene oxide and sodium dodecyl sulfate is 0.5:0.005:50:0.83:0.004.

[0085] Comparative Example 4

[0086] The difference from Example 1 is that the preparation of the anti-aging filler comprises the following steps:

[0087] S11, mix nano titanium dioxide and sodium hydroxide solution, ultrasonically disperse for 30 minutes, stir in dark place for 8 hours, transfer to a stainless steel hydrothermal reactor with polytetrafluoroethylene lining, seal and place in a blast drying oven, keep constant temperature at 145°C for 30 hours, cool to room temperature, centrifuge, wash the solid phase, dry, and calcine at 450°C for 2 hours to obtain material A; the dosage ratio of the nano titanium dioxide and sodium hydroxide solution is 0.6g:60mL; the concentration of the sodium hydroxide solution is 10mol / L;

[0088] S12, taking the material A and the silver nitrate solution, mixing, ultrasonically dispersing for 10 minutes, stirring for 8 hours, centrifuging, washing the solid phase, drying, and calcining at 450° C. for 1 hour to obtain material B; the dosage ratio of the material A to the silver nitrate solution is 0.8 g:100 mL; the concentration of the silver nitrate solution is 0.1 mol / L;

[0089] S13, mixing graphene oxide powder, material B and deionized water, ultrasonically dispersing for 1 hour, transferring to a hydrothermal reactor and reacting at 110° C. for 2 hours, cooling, centrifuging, washing and drying the solid phase to obtain material C; the mass ratio of the graphene oxide powder, material B and deionized water is 0.15:0.8:200;

[0090] S14, take the material C and deionized water, mix them, and ultrasonically disperse them for 30 minutes to obtain material D; take polyglutamic acid and sodium hydroxide solution, mix them, and stir them for 20 minutes to obtain material E; add the material E to the material D while stirring, then ultrasonically disperse it for 15 minutes, stir it at room temperature in a nitrogen atmosphere for 18, dry it, and grind it to obtain modified graphene oxide, which is the anti-aging filler; the dosage ratio of the material C, deionized water, polyglutamic acid, and sodium hydroxide solution is 0.8g:150mL:2g:50mL; the concentration of the sodium hydroxide solution is 4mg / mL.

[0091] Comparative Example 5

[0092] The difference from Example 1 is that no epoxidized soybean oil is added during the preparation of the compatibilizer.

[0093] Comparative Example 6

[0094] The difference from Example 1 is that polystyrene-block-methyl methacrylate is not added during the preparation of the compatibilizer.

[0095] Performance Testing

[0096] According to standard GB / T 7141-2008, the PC / PP alloys prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to artificial accelerated aging tests (90°C, 500h), and the elongation at break and the notched cantilever beam impact strength before and after artificial accelerated aging were measured, and the elongation at break retention rate and the impact strength retention rate were calculated. The test results are shown in Table 1 below.

[0097] Table 1

[0098] Tensile strength retention, % Impact strength retention, % Example 1 83.4 82.7 Example 2 83.7 82.8 Example 3 83.5 82.4 Comparative Example 1 78.4 79.3 Comparative Example 2 78.3 79.6 Comparative Example 3 78.9 79.1 Comparative Example 4 78.1 78.8 Comparative Example 5 77.4 74.5 Comparative Example 6 76.7 74.8

[0099] As can be seen from Table 1, the PC / PP alloys prepared in Examples 1-3 of the present application have good anti-aging properties; in Comparative Example 1, nano titanium dioxide was not added during the preparation process, resulting in a decrease in the anti-aging properties of the prepared PC / PP alloy; in Comparative Example 2, silver was not loaded during the preparation process, resulting in a decrease in the anti-aging properties of the prepared PC / PP alloy; in Comparative Example 3, polyglutamic acid was not added during the preparation process, resulting in a decrease in the anti-aging properties of the prepared PC / PP alloy; in Comparative Example 4, rod-shaped nano zinc oxide was not added during the preparation process, resulting in a decrease in the anti-aging properties of the prepared PC / PP alloy; in Comparative Example 5, epoxy soybean oil was not added during the preparation process, resulting in a decrease in the anti-aging properties of the prepared PC / PP alloy; in Comparative Example 6, polystyrene-block-methyl methacrylate was not added during the preparation process, resulting in a decrease in the anti-aging properties of the prepared PC / PP alloy.

[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an anti-aging PC / PP alloy, characterized in that: The following steps are involved: Polycarbonate, polypropylene, a compatibilizer, stearic acid, and an anti-aging filler are mixed in a high-speed mixer, and the mixture is extruded and granulated in a screw extruder to obtain the anti-aging PC / PP alloy; The preparation of the anti-aging filler comprises the following steps: S11, mix nano titanium dioxide and sodium hydroxide solution, disperse by ultrasonication, stir in the dark, keep at 145°C for 30-40h, cool to room temperature, centrifuge, wash the solid phase, dry, and calcine to obtain material A; S12, mixing the material A and the silver nitrate solution, ultrasonically dispersing, stirring, centrifuging, washing, drying, and calcining the solid phase to obtain material B; S13, mixing graphene oxide powder, material B and deionized water, ultrasonically dispersing, reacting at 110° C. for 2-3 hours, cooling, centrifuging, washing and drying the solid phase to obtain material C; S14, mixing the material C and deionized water, and ultrasonically dispersing to obtain material D; mixing polyglutamic acid and sodium hydroxide solution, and stirring to obtain material E; adding the material E to the material D while stirring, and then ultrasonically dispersing, stirring at room temperature in a nitrogen atmosphere for 18-24 hours, drying, and grinding to obtain modified graphene oxide; S15, mixing zinc oxide nanorods, sodium polyacrylate and deionized water, and dispersing by ultrasonication to obtain material F for standby use; placing the modified graphene oxide in the material F, adding sodium dodecyl sulfate, stirring in a water bath at 45° C. for 3-4 hours, filtering, and drying the precipitate to obtain the anti-aging filler; The preparation of the compatibilizer comprises the following steps: S21, mix solid hydrochloric acid and acetone, add epoxidized soybean oil, stir at 45°C for 15-20min, then cool to 40°C and continue stirring for 2-3h, add ethyl acetate and deionized water, wash the organic phase after separation, dry, filter, and remove acetone by distillation under reduced pressure to obtain material G; S22, take polystyrene-block-methyl methacrylate, inhibitor 701, and epoxy soybean oil, mix, stir for 15-20 minutes, heat to 85-95°C, add acrylic acid and triphenylphosphine, stir for 2-3 hours, heat to 110-120°C, react for 5-6 hours, cool, then introduce into butanone, filter, take the liquid phase, introduce into petroleum ether, let stand for 6-8 hours, filter, take the solid phase and dry to obtain material H; S23. In a nitrogen atmosphere, mix the material G, material H, isophorone diisocyanate and 2,2-dimethylolpropionic acid, stir at 75-85°C for 2-3h, cool to room temperature, add a mixture of sodium dodecyl sulfate-potassium persulfate-deionized water, stir for 15-20min, add methyl methacrylate and butyl acrylate, stir for 20-30min, heat to 75-85°C, stir for 4-6h, filter, and take the liquid phase to obtain the compatibilizer.

2. The method for preparing an anti-aging PC / PP alloy according to claim 1, characterized in that: The mass ratio of the polycarbonate, polypropylene, compatibilizer, stearic acid and anti-aging filler is 40-55:35-45:4-10:1-2:0.8-1.

2.

3. The method for preparing an anti-aging PC / PP alloy according to claim 1, characterized in that: In step S11, the dosage ratio of the nano-titanium dioxide and the sodium hydroxide solution is 0.6-0.8 g: 60-80 mL.

4. The method for preparing an anti-aging PC / PP alloy according to claim 1, characterized in that: In step S12, the dosage ratio of the material A to the silver nitrate solution is 0.8-1.2 g: 100-120 mL.

5. The method for preparing an anti-aging PC / PP alloy according to claim 1, characterized in that: In step S13, the mass ratio of the graphene oxide powder, material B, and deionized water is 0.15-0.25:0.8-1.2:

200.

6. The method for preparing an anti-aging PC / PP alloy according to claim 1, characterized in that: In step S14, the dosage ratio of the material C, deionized water, polyglutamic acid, and sodium hydroxide solution is 0.8-1.2 g: 150-200 mL: 2-3 g: 50-80 mL.

7. The method for preparing an anti-aging PC / PP alloy according to claim 1, characterized in that: In step S15, the mass ratio of the zinc oxide nanorods, sodium polyacrylate, deionized water, modified graphene oxide, and sodium dodecyl sulfate is 0.5-0.6: 0.005-0.006: 50: 0.83-1.25: 0.004-0.

006.

8. An anti-aging PC / PP alloy obtained by the preparation method of an anti-aging PC / PP alloy as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Anti-aging PC / PTT / PP plastic alloy and preparation method thereof

    CN105237981A

  • High-strength instrument shell and production process thereof

    CN112533403A

  • Polycarbonate / polypropylene alloy material and preparation method thereof

    CN113943458A